Victim or master of HRM implementation: the frontline manager conundrum. (11th October 2021) - Townsend, Keith; Dundon, Tony; Cafferkey, Kenneth; Kilroy, Jennifer
Abstract : This article reflects on the evolution of the frontline manager as an important anchor in the exploration and debate of human resource management. An earlier theoretical lens presented in the Asia‐Pacific region is given fresh influence through a review of recent literature. Ultimately, the review extends the contribution of the frontline management 'master and victim' conundrum to an explanatory framework of human resource adoption at the frontline. While it is well recognised that the manager is often squeezed between the aspirations of a HR system and the realities of frontline worker dynamics, the specific influencing factors are often overlooked. This article addresses that gap by providing an explicit framework to highlight the critical role that agency and policy enactment play in determining the stylistic preferences of frontline management. Ultimately, four distinct manifestations of frontline management are explored and recommended for further human resource management research in the region.